Readiness of sports infrastructure in supporting of provincial sports events - Ichlasul Amal; Endarman Saputra; Ceppy Pradana Putra (Universitas Sriwijaya, 2025)
Research Problems: Provincial Sports Week Jambi 2026 in Tanjung Jabung Barat requires a well-prepared Sports Centre as the main venue. Research Objectives: This study aimed to determine the state of sports centre facilities and infrastructure in Tanjung Jabung Barat towards the Provincial Sports Week Jambi in 2026. Methods: This study uses a quantitative descriptive approach to assess the facilities, management, and sustainability of the Sport Centre. The sample used was 50 respondents with a sampling technique using Purposive Sampling. The data analysis method uses quantitative and descriptive analysis, using SPSS Version 29. Results: The research shows that the infrastructure indicator received an answer in the